2023
DOI: 10.1159/000534620
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine and Alcohol: A Review of in vivo PET and SPECT Studies

Gianna Spitta,
Maria Garbusow,
Ralph Buchert
et al.

Abstract: <b><i>Background:</i></b> Alcohol-associated alterations of the dopaminergic (DA) system have been investigated via functional single-photon emission tomography (SPECT) positron emission tomography (PET) and imaging methods over many years, investigating presynaptic or postsynaptic markers, such as DA receptor and DA transporter availability, both with and without challenge. This review summarizes SPECT and PET studies on different levels of alcohol consumption to support the dimensiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 165 publications
(359 reference statements)
2
3
1
Order By: Relevance
“…We were able to expand our previous finding of reduced dopamine D2/3 receptor availability (BP) in AD patients compared to LR and HR controls 21 using the AS, LS and SMS that were found to be implicated in earlier studies 44 . More precisely, we found reduced BP of AD patients in the dorsal striatum, which is in line with a recent meta‐analysis and review 12,13 . Interestingly, according to our previous study, we did not find an impairment of dopamine D2/3 availability in the ventral striatum, which is in contrast to some previous studies 10 .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…We were able to expand our previous finding of reduced dopamine D2/3 receptor availability (BP) in AD patients compared to LR and HR controls 21 using the AS, LS and SMS that were found to be implicated in earlier studies 44 . More precisely, we found reduced BP of AD patients in the dorsal striatum, which is in line with a recent meta‐analysis and review 12,13 . Interestingly, according to our previous study, we did not find an impairment of dopamine D2/3 availability in the ventral striatum, which is in contrast to some previous studies 10 .…”
Section: Discussionsupporting
confidence: 88%
“…Striatal dopamine (DA) is released during acute alcohol intake, which leads to the rewarding effects of alcohol and may reinforce alcohol use 9 . Chronic alcohol use has been associated with reduced dopamine D2/3 receptor sensitivity and availability in the striatum, 10,11 which has been confirmed in a recent meta‐analysis and a review 12,13 …”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…After establishing that DAergic striatal covariance networks possessed organizational features, we investigated potential alterations in AUD, as substance use disorders are believed to disrupt DAergic system function (Koob and Volkow 2010). Our analyses showed that the covariance structure of the AUD group network is indeed altered, showing less organization and lower network degree, density, and strength (Figure 2), supporting previous literature that alcohol dependence disrupts dopaminergic function in the striatum (Spitta et al 2023), while providing novel insight into the inter-regional relationships of DAergic function. We identified three edges in which covariance significantly differed between AUD and CON: ipsilateral left hemisphere nucleus accumbens shell and anterior caudate, and contralateral left accumbens core and right hemisphere accumbens shell and core (Figure 2A).…”
Section: Discussionsupporting
confidence: 86%